2014
DOI: 10.1016/j.tibs.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin and beyond: the multitasking roles for SIRT6

Abstract: In recent years there has been a large expansion in our understanding of SIRT6 biology, including its structure, regulation, biochemical activity and biological roles. SIRT6 functions as an ADP-ribosylase and NAD+-dependent deacylase of both acetyl groups and long-chain fatty acyl groups. Through these functions SIRT6 impacts cellular homeostasis by regulating DNA repair, telomere maintenance and glucose and lipid metabolism, thus affecting diseases such diabetes, obesity, heart disease, and cancer. Such roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
284
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(294 citation statements)
references
References 77 publications
(130 reference statements)
8
284
0
2
Order By: Relevance
“…Emerging studies have shown that Sirt6 is a key regulator of genome stability, glucose homeostasis, metabolism and inflammation (9). It governs diverse cellular functions, such as transcription, telomere integrity and DNA repair (9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Emerging studies have shown that Sirt6 is a key regulator of genome stability, glucose homeostasis, metabolism and inflammation (9). It governs diverse cellular functions, such as transcription, telomere integrity and DNA repair (9).…”
Section: Discussionmentioning
confidence: 99%
“…It governs diverse cellular functions, such as transcription, telomere integrity and DNA repair (9). Mouse pups with whole-body Sirt6 with lipopolysaccharide resulted in downregulation of Rspo1 mRNA ( Supplementary Figure 3) and protein expression in colons ( Figure 7C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The natural product resveratrol activates SIRT1 and has led to the development of more potent SIRT1 activating compounds, which are now in development for the treatment of age-related diseases [128]. SIRT6 is an ADP-ribosylase as well as a protein deacetylase and plays a key role in regulating DNA repair, telomere maintenance and metabolic homeostasis and, like SIRT1, is linked to extension of lifespan [129]. Reduced SIRT6 has been implicated in COPD, atherosclerosis, obesity and type 2 diabetes [125,129].…”
Section: Defective Anti-ageing Molecules and Pathwaysmentioning
confidence: 99%